2011
DOI: 10.1002/dvdy.22741
|View full text |Cite
|
Sign up to set email alerts
|

Atlas of Wnt and R‐spondin gene expression in the developing male mouse lower urogenital tract

Abstract: Prostate development is influenced by β-catenin signaling, but it is unclear which β-catenin activators are involved, where they are synthesized, and whether their mRNA abundance is influenced by androgens. We identified WNT/β-catenin-responsive β-galactosidase activity in the lower urogenital tract (LUT) of transgenic reporter mice, but β-galactosidase activity differed among the four mouse strains we examined. We used in situ hybridization to compare patterns of Wnts, r-spondins (Rspos, co-activators of β-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
78
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(88 citation statements)
references
References 69 publications
10
78
0
Order By: Relevance
“…In particular, several Wnt ligands are upregulated during the period of prostatic bud formation Pritchard et al, 2009;Zhang et al, 2006). Furthermore, analyses using sensitive transgene reporters have shown that Wnt signaling activity is present in the mouse UGM prior to prostate budding and subsequently in both the mesenchyme and ductal tips during outgrowth (Kruithof-de Julio et al, 2013;Mehta et al, 2011). Consistent with these findings, downstream targets of canonical Wnt signaling such as Lef1 are expressed in epithelial cells of prostate ductal tips (Francis et al, 2013;Mehta et al, 2013;Wu et al, 2011).…”
Section: The Andromedin Hypothesismentioning
confidence: 74%
“…In particular, several Wnt ligands are upregulated during the period of prostatic bud formation Pritchard et al, 2009;Zhang et al, 2006). Furthermore, analyses using sensitive transgene reporters have shown that Wnt signaling activity is present in the mouse UGM prior to prostate budding and subsequently in both the mesenchyme and ductal tips during outgrowth (Kruithof-de Julio et al, 2013;Mehta et al, 2011). Consistent with these findings, downstream targets of canonical Wnt signaling such as Lef1 are expressed in epithelial cells of prostate ductal tips (Francis et al, 2013;Mehta et al, 2013;Wu et al, 2011).…”
Section: The Andromedin Hypothesismentioning
confidence: 74%
“…Yet in developing mouse prostate, Wif1 is expressed in UGM and UGE and overlaps WNT/␤-cateninresponsive Axin2 and Lef1 (lymphoid enhancer binding factor 1) expression (14,15,19). Coexpression of Wif1 with abundant WNT/␤-catenin-responsive mRNA expression would not be predicted if WIF1 functioned as a strong WNT/␤-catenin inhibitor in control UGS.…”
Section: Exogenous Wif1 Does Not Change the Pattern Of Wnt/␤-catenin mentioning
confidence: 99%
“…Coexpression of Wif1 with abundant WNT/␤-catenin-responsive mRNA expression would not be predicted if WIF1 functioned as a strong WNT/␤-catenin inhibitor in control UGS. We tested whether prostatic bud-enhancing concentrations of exogenous WIF1 protein visibly altered the pattern of WNT/␤-catenin-responsive Axin2 and Lef1 mRNA within and immediately surrounding prostatic bud tips in which both mRNAs were detected previously (19). E14.5 male UGSs were grown for 4 d in UGS organ culture media containing DHT and graded recombinant WIF1 protein concentrations.…”
Section: Exogenous Wif1 Does Not Change the Pattern Of Wnt/␤-catenin mentioning
confidence: 99%
See 2 more Smart Citations